THE IMPACT OF GEOPOLITICS ON MARKET VOLATILITY: MITIGATION STRATEGIES FOR GLOBAL BUSINESSES - Sigit Sugiardi; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Global geopolitical uncertainties are increasingly fuelling volatility in the world's financial and economic markets. This research aims to analyse the impact mechanisms of geopolitical events-such as military conflicts, economic sanctions, and diplomatic tensions-on market volatility and formulate effective mitigation strategies for global businesses. Using the literature review method, this study collects and analyses various scientific literature, financial institution reports, and recent case studies relevant to the topic. The results show that geopolitical risks contribute significantly to fluctuations in stock prices, exchange rates, and commodity prices, especially in emerging economies that are integrated with global markets. To face these challenges, mitigation strategies such as portfolio diversification, real-time risk monitoring, supply chain strengthening, and contingency planning have proven effective in enhancing business resilience. This research recommends that global businesses adopt adaptive and comprehensive risk management to minimise the negative impact of geopolitical uncertainty and maintain business sustainability and competitiveness in international markets.